Retrospective analysis of equine traumatic injury: patterns and insights - Abdul Rahim, Zulfitri Naim; Mohd Adzahan, Noraniza; Abdul Razak, Intan Shameha; Zakaria, Zunita; Roselan, Puteri Rose Camelia (Universiti Putra Malaysia, 2025)
Traumatic injury is a catastrophic and second most frequent emergency condition that is significantly labor intensive and expensive to treat, raising a welfare concern in the equine industry. Even though the incidence is high, there is still a lack of data addressing the prevalence of these traumatic injuries, particularly in Malaysia. Therefore, this study aims to describe the occurrence and patterns of the traumatic injuries experienced by the subpopulation of horses in Malaysia. The records of horses reported to the University Veterinary Hospital, Universiti Putra Malaysia between January and December 2023 were reviewed to determine traumatic injury cases and all data were analysed descriptively. Among 422 patient medical records, 99 horses (23.0%) were reported to have sustained a total of 107 traumatic injuries. Majority of the injuries were reported to occur in the stable (26.2%), while being ridden (18.7%), and during the competition (18.7%), in which most of the cases were associated with wounds (60.7%), but the occurrence of fractures (9.3%) and injured ligaments or tendons (15.0%) were also high. Occurrence of being kicked by another horse (11.2%) and penetration by sharp objects (11.2%) were the most common mechanisms of injury, whereby forelimbs (38.8%) and hindlimbs (29.8%) were injured the most, commonly at the distal aspect. This data will enable horse owners and veterinarians to employ better traumatic injury– preventative strategies.